2017
DOI: 10.1063/1.4981206
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the inertial confinement time in a magnetically driven implosion

Abstract: We report on direct, radiographic measurement of the stagnation phase of a magnetically driven liner implosion. The liner is filled with liquid deuterium and imploded to a minimum radius of 440 μm (radial convergence ratio of 7.7) over 300 ns, achieving a density of ≈10 g/cm3. The measured confinement time is ≈14 ns, compared to 16 ns from 1D simulations. A comparison of measured density profiles with 1D and 2D simulations shows a deviation in the reflected shock trajectory and the liner areal density. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Another related fundamental question concerns the effect of MRT on fuel assembly and confinement. Radiographic experiments enabling direct measurements of the inertial confinement time, τ , and pressure-time product, Pτ , demonstrated that areal density variations due to MRT can decrease both the inertial confinement time and attainable fuel pressures [88]. Furthermore, MRT weakens confinement in the bubble regions via mass transport to the spikes, creating regions susceptible to 'aneurysms' that can lead to rapid pressure loss of the fuel [88,89].…”
Section: Instability Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another related fundamental question concerns the effect of MRT on fuel assembly and confinement. Radiographic experiments enabling direct measurements of the inertial confinement time, τ , and pressure-time product, Pτ , demonstrated that areal density variations due to MRT can decrease both the inertial confinement time and attainable fuel pressures [88]. Furthermore, MRT weakens confinement in the bubble regions via mass transport to the spikes, creating regions susceptible to 'aneurysms' that can lead to rapid pressure loss of the fuel [88,89].…”
Section: Instability Developmentmentioning
confidence: 99%
“…Radiographic experiments enabling direct measurements of the inertial confinement time, τ , and pressure-time product, Pτ , demonstrated that areal density variations due to MRT can decrease both the inertial confinement time and attainable fuel pressures [88]. Furthermore, MRT weakens confinement in the bubble regions via mass transport to the spikes, creating regions susceptible to 'aneurysms' that can lead to rapid pressure loss of the fuel [88,89]. Figure 11 shows radiographic images capturing the development of an aneurysm in a beryllium liner confining a high-pressure deuterium fuel.…”
Section: Instability Developmentmentioning
confidence: 99%
“…The fast (100-ns) imploding liner-fuel system can then be considered an inertial confinement fusion (ICF) "target." Imploding a metal liner containing fuel is the technique employed by the magnetized liner inertial fusion (MagLIF) concept [7], [8] presently being investigated numerically [7], [8], [41]- [44] and experimentally [9], [10], [45]- [52] using the Z facility at Sandia. As described by Eq.…”
Section: A Simple Picture Of a Pulsed-power-driven Hedp Experimentsmentioning
confidence: 99%
“…In the ICF, the disturbance at the hotspot-fuel interface originates from its initial perturbation, the feedthrough of the perturbation on the ablation surface and the driven inhomogeneity (Hsing & Hoffman 1997;Weir, Chandler & Goodwin 1998;Shigemori et al 2002;Regan et al 2004;Haan et al 2011;Simakov et al 2014;Knapp et al 2017;Desjardins et al 2019). Milovich et al (2004) showed that the feedthrough of the ablation surface leads to a significant decrease in the implosion efficiency of a double-shell ignition target.…”
Section: Introductionmentioning
confidence: 99%